Systematic quantitative modeling of the natural history of Aicardi syndrome: A cross sectional study of 245 published cases - Oliver Y. Urban; Jan H. Driedger; Sven F. Garbade; Georg F. Hoffmann; Stefan Kölker; Markus Ries; Steffen Syrbe (Orphanet Journal of Rare Diseases)
Abstract Purpose Aicardi syndrome is a rare epileptic encephalopathy, almost exclusively affecting girls. It was first described as a triad of infantile spasms, chorioretinal defects and agenesis of the corpus callosum. The etiology remains unknown and there is uncertainty on best practice therapy and outcome. We aimed at defining quantitative clinical endpoints that will inform future research and clinical trials. Methods Quantitative natural history modeling of cases with Aicardi syndrome from published clinical reports. Main outcome measures were age at disease onset, survival and diagnostic delay. Phenotypic features of affected individuals as well as neuroradiological and ophthalmological features were descriptively stated. STROBE criteria were respected. Results Two hundred forty-five cases were available for analysis. Median age at disease onset was 2.2 months. Median diagnostic delay was 1 month. Mortality was estimated with 6% at 1 and 17% at 5 years of age. 60% of children showed the classic clinical features, while 40% met the revised diagnostic criteria. We delineate possible predictors of disease severity and of seizure control. Conclusion We provide natural history data including geographical localization of 245 published patients with Aicardi syndrome. Quantitative history modeling in rare epileptic encephalopathies will help to raise disease awareness and facilitate future clinical trials as one core element of quantitative systems pharmacology.